2021
DOI: 10.1039/d1fo00747e
|View full text |Cite
|
Sign up to set email alerts
|

DHA-enriched phospholipids from large yellow croaker roe regulate lipid metabolic disorders and gut microbiota imbalance in SD rats with a high-fat diet

Abstract: Large yellow croaker roe phospholipids (LYCRPLs) has great nutritional value because of containing rich docosahexaenoic acid (DHA), which is a kind of n-3 polyunsaturated fatty acids (n-3 PUFAs). In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 83 publications
2
18
0
Order By: Relevance
“…Lu et al. (2021) further showed that DHA‐enriched phospholipids (PL) from large yellow croaker roe could reduce the body weight of rats without affecting their daily food intake, and our results were consistent with these studies.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Lu et al. (2021) further showed that DHA‐enriched phospholipids (PL) from large yellow croaker roe could reduce the body weight of rats without affecting their daily food intake, and our results were consistent with these studies.…”
Section: Resultssupporting
confidence: 90%
“…Similarly, Gao et al (2021) showed that EPA/DHAphosphatidylcholine (PC) from squid roes could reduce the body weight of mice without affecting their daily food intake. Lu et al (2021) further showed that DHA-enriched phospholipids (PL) from large yellow croaker roe could reduce the body weight of rats without affecting their daily food intake, and our results were consistent with these studies.…”
Section: Effect Of Dha-ps On Body Weight Gain and Food Intake Of Micesupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, several studies have also proved that marine phospholipids exert anti-obesity effects. For example, Lu et al reported that phospholipids from large yellow croaker roe could regulate lipid metabolism, and improve gut microbiota disorder in HFD-fed rats [ 29 ]. Phospholipids from krill oil were proved to lower body weight gain, mesenteric adipose tissue, and hepatic lipid content [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian studies have suggested that appropriate levels of DHA could improve the gut microbiota disorder caused by high-fat diet (HFD) or chronic stress ( 17 20 ). The health-promoting effects of DHA, such as alleviating hyperglycemia, insulin resistance, and lipid metabolism abnormalities, are partly mediated by the modulation of gut microbiome and bacterial metabolites ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%